Reforma al Código Orgánico Integral Penal, de los delitos informáticos - Rojas Ordóñez, Milton (2015)
The title of the research was expressed. It was justified: the importance, scientific, seen from the perspective: social, institutional, and prior to obtaining the professional title researcher. The general objective was raised: "Making a research, doctrinal, social and legal study of the most common computer crimes not under the Penal Code Integral Ecuador; to incorporate by COIP reform"; Three specific objectives which were derived; objectives were met. The methods used in the research were: scientific, historical, inductive-deductive and comparative-analytical. As techniques and instruments are applied: structured interview, with the respective questionnaire to a sample of thirty people, including judges, prosecutors and lawyers in free practice. With positive results proved the hypothesis proposed; and as a general conclusion, it was established that the current Ecuadorian Code of Integral Penal provides for the definition of certain computer crimes, but many others that are presented today in Ecuador and the world, have not yet been incorporated in the Code, and therefore, they must be inserted in the COIP, through a reform of that body of law